IMPLIKASI DESENTRALISASI FISKAL TERHADAP AKABA DAN APM SD/MI DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2007-2010 - Mahocca Swangga Purusa; Hadi Sasana (Diponegoro Journal of Economics, 2013)
Implementation of the regional autonomy through fiscal decentralization is expected to improve the quality of public services. Health and education Outcomes is one measure that can be used to view the quality of public services. Health Outcomes can be seen through the toddler mortality rate (AKABA), whereas educational outcomes can be seen through pure participation rate (APM) SD/MI. This study aims to examine empirically the influence of fiscal decentralization to the toddler mortality rate (AKABA) and pure participation rate (APM) SD/MI in counties/cities Central Java Province. The type of data in this research is panel data using analysis methods with the approach of the fixed effect model (FEM). Panel data in this study covers 35 counties/cities in Central Java province, in the period 2007 to 2010. The result of this study shows that the fiscal decentralization had significantly negative impact on toddler mortality rate and significant positive to pure participation rate SD/MI. Fiscal decentralization is able to reduce the toddler mortality rate as much as 31,8 per 1.000 live births, increase pure participation rate SD/MI as much as 0.05 percent every 1 percent increase in the degree of fiscal decentralization.